A synergistic flame retardant system based on expandable graphite, aluminum (Diethyl-)polyphospinate and melamine polyphosphate for polyamide 6 - Tomiak, Florian; Schoeffel, Angelina; Rathberger, Klaus; Drummer, Dietmar (Polymers, 2021)
Expandable graphite (EG), aluminum (diethyl)polyphosphinate (AlPi) and melamine polyphophate (MPP) was used as flame retardant multi-material additive in a polyamide 6 (PA6) matrix. Flame inhabitation performances were conducted by cone calorimeter, LOI and UL-94 tests, synergisms identified analyzed by TGA-FTIR and TGA-GC/MS and effects found were compre-hensively discussed. SEM images were used for char residue characterization. For PA6 containing 20 wt.% EG and 5 wt.% AlPi/MPP (3:2), a well working synergism in limiting oxygen indices could be identified exhibiting the highest oxygen index (OI) measured: 46%. The study shows that the synergism due to the partial substitution of EG by AlPi/MPP can be attributed to two effects: (1) When PA6/AlPi/MPP mixtures decompose predominantly CO2 evaporates in early decomposition stages. CO2 evaporations was found to be sensitive to the heating rate applied, whereas specifically high heating rates increased the CO2 yield measured. (2) Solid decomposition products of AlPi/MPP act as “glue” between expanded graphite and thus increase the mechanical residue stability.
CRIS-Team Scopus Importer:2021-08-27
Keywords: AlPi; Aluminum (diethyl-)polyphosphinate; Expandable graphite; Flame retardant multi-material system; Heating rate; Melmanin polyphosphate; MPP; Nylon 6; PA6; Synergistic effect